Respuesta biologica de los policultivos de tilapia roja oreochromis sp y camarón litopenaeus vannamei en jaulas a diferentes densidades - Freire Vega, Darwin Vinicio (2008)
The investigation work was carried out it in the Property "Mariaeliza" of property of the one. Engineer Luís Matute, located in the parish Palmales, Canton Sands, Via Puyango. To define population's appropriate densities in the policultivos between shrimp and tilapia. According to the factor of nutritious conversion the Treatment II are better with 1,33 followed by the treatment III with 1,34; and the treatment I with 1,36.La survival was better in the treatment III with 95,5% in tilapia and 64,4% in shrimp. As for the pounds harvested tilapia/camarón for cage the treatment III were better with 11,61 pounds of tilapia more 0,41 pounds of shrimp giving a total of 12,02 pounds of the product. The appropriate density for a policultivo (tilapia/shrimp) basing us on the results of our investigation is of (30 tilapias/60 camarones)/m3.